Target therapy in treatment of HER2-positive breast cancer - A. S. Belokhvostova; I. A. Smirnova; A. A. Enileeva (Сибирский онкологический журнал)
The breast cancer (BC) wins first place in structure of oncological incidence of the female population around the world. The special place is occupied by tumors with a superfluous expression of HER2 of a factor which is defined at 25–30 % of patients. Interest to suchpatients is defined by an aggressive course of disease, an early metastasis, resistance to chemo-and hormonotherapy. The main targeted drugs registered in the Russian Federation for treatment of HER2-positive BC is Trastuzumab (herceptin®). The presented review contains data of researches on application of a preparation of herceptin in various schemes of chemotherapy. Studying of a combination of trastuzumab with cytostatics, other targeted drugs proceeds at various stages of tumoral process.